Answering the Call of Duty: Everyday encounters with the popular geopolitics of military-themed videogames. (March 2018) - Bos, Daniel
Abstract: Despite a growing interest in the way the media and popular culture shape geopolitical identities and subjectivities, current scholarship has overlooked the spaces, practices and experiences in which geopolitical sensibilities are made meaningful in everyday life. Whilst previous scholarship considers popular consumption as purely an interpretative act, this paper considers the event of geopolitical consumption, noting the social, material, and spatial contexts in which popular geopolitics is encountered in everyday life. In making this case the paper draws attention to military-themed videogames as an important everyday cultural artefact that shapes popular understanding of geopolitics. A multi-method approach is adopted involving 32 interviews and the collection of video ethnographic data, to reveal the everyday happenings of playing virtual war. The paper makes three contributions. Firstly, by drawing attention to the practices and performances of players, it shows how players are predisposed to varying engagements with the geopolitical and avoids assuming the effects and significance of popular geopolitical representations and narratives. Secondly, a focus on the everyday spaces of consuming popular culture broadens understandings into the ways the domestic setting shapes, and is shaped by, popular geopolitical consumption and in which private, public and virtual spheres interact. Thirdly, the paper illustrates the contingency of wider social, material and technological relations which amplify, yet also disrupt, these affective geopolitical encounters.